2020
DOI: 10.1002/ajs4.134
|View full text |Cite
|
Sign up to set email alerts
|

Children and safety in Australian policy: Implications for organisations and practitioners

Abstract: Child safety is now a national policy priority in Australia. Extensive enquiries and reviews have escalated legislative and policy responses focused on developing, maintaining and monitoring “child safe” organisations. The recommendations of the Royal Commission into Institutional Responses to Child Sexual Abuse point to the importance of cultural conditions within organisations in supporting child safety and the need for responsive change in some organisations. Drawing on a recent policy analysis, undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Other studies support these fndings, noting that young people in residential care want adults to involve them in codesigning efective strategies to navigate peer relationships and peer pressure [4,28]. Recent policy analysis added that a paradigm shift is needed in the current childrights approach, from positioning young people in OOHC as passive recipients of adults' protection to recognising their agency to communicate their views and direct adults' responses [40]. However, as practitioners in our study revealed, systemic pressures reduce their control over matching decisions and prevent them from meaningfully involving young people.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies support these fndings, noting that young people in residential care want adults to involve them in codesigning efective strategies to navigate peer relationships and peer pressure [4,28]. Recent policy analysis added that a paradigm shift is needed in the current childrights approach, from positioning young people in OOHC as passive recipients of adults' protection to recognising their agency to communicate their views and direct adults' responses [40]. However, as practitioners in our study revealed, systemic pressures reduce their control over matching decisions and prevent them from meaningfully involving young people.…”
Section: Discussionmentioning
confidence: 99%